Quantification of Ultrasound Correlation‐Based Flow Velocity Mapping and Edge Velocity Gradient Measurement. (1st October 2013) - Park, Dae Woo; Kruger, Grant H.; Rubin, Jonathan M.; Hamilton, James; Gottschalk, Paul; Dodde, Robert E.; Shih, Albert J.; Weitzel, William F.
Abstract : This study investigated the use of ultrasound speckle decorrelation‐ and correlation‐based lateral speckle‐tracking methods for transverse and longitudinal blood velocity profile measurement, respectively. By studying the blood velocity gradient at the vessel wall, vascular wall shear stress, which is important in vascular physiology as well as the pathophysiologic mechanisms of vascular diseases, can be obtained. Decorrelation‐based blood velocity profile measurement transverse to the flow direction is a novel approach, which provides advantages for vascular wall shear stress measurement over longitudinal blood velocity measurement methods. Blood flow velocity profiles are obtained from measurements of frame‐to‐frame decorrelation. In this research, both decorrelation and lateral speckle‐tracking flow estimation methods were compared with Poiseuille theory over physiologic flows ranging from 50 to 1000 mm/s. The decorrelation flow velocity measurement method demonstrated more accurate prediction of the flow velocity gradient at the wall edge than the correlation‐based lateral speckle‐tracking method. The novelty of this study is that speckle decorrelation‐based flow velocity measurements determine the blood velocity across a vessel. In addition, speckle decor‐relation‐based flow velocity measurements have higher axial spatial resolution than Doppler ultrasound measurements to enable more accurate measurement of blood velocity near a vessel wall and determine the physiologically important wall shear.